EP972 Precision medicine program for epithelial ovarian carcinoma (EOC): first year experience at clínica universidad de navarra (CUN). (1st November 2019) - Sánchez Lorenzo, L; Espinosa Mariscal, I; Chacón, E; Patiño-García, A; Espinós, J; Aramendia, JM; Castellanos, T; Vázquez, D; Minguez, JÁ; Alkorta-Aramburu, G; Idoate, MÁ; Alcázar, JL; et al.
Abstract : Introduction/Background: Next Generation Sequencing (NGS) technology enables for the simultaneous study of multiple gene alterations in the patient's tumor with potential implications for genetic risk assessment, prognosis, and therapy. Methodology: CUN opened a new hospital in Madrid in January 2018. During the first year, new patients (pts) with EOC at both CUN were offered to perform a NGS-based tumor testing. Local test consisted in Oncomine Comprehensive Assay (161 gene panel, ThermoFisher Scientific) and external test in Foundation Medicine (Foundation Medicine, Cambridge, MA). This is a descriptive analysis of the rate of implementation, the molecular alterations found, and the therapeutic implications derived. Results: 104 new pts were evaluated from January 1st until December 31st. 5 (4.80%) LOGSOC, 81 (77.89%) HGSOC, 11 (10.58%) CCC, 6 (5.77%) Endometrioid, 1 (0.96%) Mucinous. 44 pts with primary disease and 60 pts with recurrent disease. All but two patients were tested with Oncomine with a median turn-around time of 14 days. Table shows the rate of patients tested according to histology and context of disease. Subtype N Tested in First Line Tested in recurrence. LGSOC 5 2/2 (100%) 1/3 (33.33%). HGSOC 81 17/34 (50%) 14/47 (29, 78%). Endometrioid 6 1/2 (50%) 0/4 (0%). CCC 11 3/6 (50%) 1/5 (20%). Mucinous 1 0/0 0/1 (0%). TOTAL 104 23/44 (52.57%) 16/60 (26.67%). sBRCA mutation was detected in 6/23 primary diagnosis (26.1%) and 2 pts (both gBRCAwt) received olaparib maintenance after SOLO-1 publication. In the recurrent setting, 5/16 pts (31.25%) had at least one actionable mutation with available matched therapy and 3 pts received matched therapy (18.76%). Non-BRCA genes associated to hereditary EOC were detected in 4 pts. Conclusion: Integration of a precision medicine program with NGS tumor testing was feasible in routine practice in a private university hospital. This is an ongoing program and the rate of tumor testing should improve in subsequent years. Disclosure: Advisory for Roche and Tesaro.